2001
DOI: 10.1002/lsm.1042
|View full text |Cite
|
Sign up to set email alerts
|

830‐nm irradiation increases the wound tensile strength in a diabetic murine model*

Abstract: Low-power laser irradiation at 830 nm significantly enhances cutaneous wound tensile strength in a murine diabetic model. Further investigation of the mechanism of LLLT in primary wound healing is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 25 publications
7
85
0
9
Order By: Relevance
“…the subgroups not given laser treatment presented lower and statistically significant mean collagen percentages, in comparison with the treated subgroups. These results corroborate studies 5,8,11,12,13 in which laser treatment accelerated the wound healing process, with increased production of collagen, a substance that is essential for wound repair. When the results obtained from the control subgroups were analyzed and compared, it was observed that the treated non-diabetic subgroup presented a higher and statistically significant collagen fiber percentage, in comparison with the untreated diabetic subgroup.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…the subgroups not given laser treatment presented lower and statistically significant mean collagen percentages, in comparison with the treated subgroups. These results corroborate studies 5,8,11,12,13 in which laser treatment accelerated the wound healing process, with increased production of collagen, a substance that is essential for wound repair. When the results obtained from the control subgroups were analyzed and compared, it was observed that the treated non-diabetic subgroup presented a higher and statistically significant collagen fiber percentage, in comparison with the untreated diabetic subgroup.…”
Section: Discussionsupporting
confidence: 89%
“…We believe that this alteration in healing response may be explained by the action of the laser, as reported by several researchers. 6,8,11,12 Analysis of the results from the fourteenth days after wounding showed increased mean collagen percentages in comparison with the seventh day. However, only the nondiabetic group presented a statistically significant result.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some of the animal studies investigating the effects of LLLT on wound healing have found similar results to the ones found in the in vitro studies, ranging from decreased inflammation and increased collagen and granulation tissue in the wound bed to increased tensile strength and faster epithelization [20][21][22][23].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelsupporting
confidence: 64%